Konseling KIPAS dalam Konteks Budaya Indonesia: Studi Literatur tentang Hakikat Manusia, Mekanisme Perubahan, dan Struktur Teoretis - Daniyatillah Daniyatillah; Budi Purwoko; Bakhrudin All Habsy (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
The Intensive Progressive Adaptive Structure Counseling (KIPAS) model was developed in response to the need for counseling practices that are able to adapt to the dynamics of individual development and environmental contexts without abandoning a directed framework. This study aims to describe the theoretical foundation of KIPAS by reviewing views on human nature, mechanisms of psychological change, and the theoretical structure that forms this model. The method used is a literature study through a review of KIPAS books, relevant counseling theories, and related scientific publications. The results of the study indicate that KIPAS is based on the integration of humanistic, cognitive-behavioral, and systemic principles that together form a counseling approach that is in-depth, gradual, adaptive, and structured. The mechanism of change in KIPAS occurs through increased self-understanding, active involvement of the counselee, and the use of intervention strategies tailored to the client's developmental responses. The theoretical structure of KIPAS ensures that the counseling process remains consistent with direction and goals. This study concludes that KIPAS has a strong theoretical foundation and is relevant for application in various educational, clinical, and organizational contexts.